If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 1 = 2(2x + 7) Reorder the terms: 1 + 5x = 2(2x + 7) Reorder the terms: 1 + 5x = 2(7 + 2x) 1 + 5x = (7 * 2 + 2x * 2) 1 + 5x = (14 + 4x) Solving 1 + 5x = 14 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 1 + 5x + -4x = 14 + 4x + -4x Combine like terms: 5x + -4x = 1x 1 + 1x = 14 + 4x + -4x Combine like terms: 4x + -4x = 0 1 + 1x = 14 + 0 1 + 1x = 14 Add '-1' to each side of the equation. 1 + -1 + 1x = 14 + -1 Combine like terms: 1 + -1 = 0 0 + 1x = 14 + -1 1x = 14 + -1 Combine like terms: 14 + -1 = 13 1x = 13 Divide each side by '1'. x = 13 Simplifying x = 13
| -12x+3x-109=143 | | 981+(45g*9)/(5*5)+9514=900000 | | 2+-5+-3=-6 | | -4(2y-3)-y=-2(y-5) | | 2+-5+-3= | | 41/45-1/27 | | 5x(6)-4= | | 3a-4a=4 | | -8=x/-7-10 | | -8=x/-7-10 | | X-6+x=10 | | -(-9)-5+(4)= | | -75+9x-x=69 | | 7/5*5/14 | | 42=7(x+4) | | 2.6(-2-8x)=-6-19.4x | | 0.50x+0.30(40)=0.25(134) | | x=(2y+5)-50 | | -2x^2+3x+4=13x-5x^2+1 | | 3+2z=5z-3-3z+6 | | 4c-19=17 | | -4c-9.6+5c=o | | -75+9x-x=9 | | 4-i(3b-8)=2b-17 | | 8x-3x+2=x-9+11 | | 2q^2+2q+24=0 | | 2b+3b=-10 | | 70+11x+11=180 | | (3x/4)-(1/3)=1-(2/3)-(1/6) | | 70+11x=180 | | 8x-x+2=x-9+11 | | 0x-4=6 |